2017
DOI: 10.1016/j.paid.2017.04.024
|View full text |Cite
|
Sign up to set email alerts
|

Creature of Habit: A self-report measure of habitual routines and automatic tendencies in everyday life

Abstract: Our daily lives involve high levels of repetition of activities within similar contexts. We buy the same foods from the same grocery store, cook with the same spices, and typically sit at the same place at the dinner table. However, when questioned about these routine activities, most of us barely remember the details of our actions. Habits are automatically triggered behaviours in which we engage without conscious awareness or deliberate control. Although habits help us to operate efficiently, breaking them r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
164
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 133 publications
(183 citation statements)
references
References 66 publications
19
164
0
Order By: Relevance
“…Participants reported that the task became simpler and easier to perform throughout the training, corroborating the assumption that perceived complexity of a behavior is also an element that influences the extent to which automaticity is attained (McCloskey and Johnson, 2019). In agreement with recent questionnaire methods for parsing components of habits (e.g., Ersche et al, 2017), we observed both routine (evidenced by the anti-correlation in app engagement across different daily time periods) and automaticity (evidenced by a combination of an asymptotic performance and responsiveness in the absence of cues).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Participants reported that the task became simpler and easier to perform throughout the training, corroborating the assumption that perceived complexity of a behavior is also an element that influences the extent to which automaticity is attained (McCloskey and Johnson, 2019). In agreement with recent questionnaire methods for parsing components of habits (e.g., Ersche et al, 2017), we observed both routine (evidenced by the anti-correlation in app engagement across different daily time periods) and automaticity (evidenced by a combination of an asymptotic performance and responsiveness in the absence of cues).…”
Section: Discussionsupporting
confidence: 82%
“…Previously, self-reported questionnaires have been used to investigate aspects of habits distinguishing between routine and automatic tendencies in humans (Gardner et al, 2012;Ersche et al, 2017). These are useful but do depend on self-report rather than providing more objective measures of habits.…”
Section: Introductionmentioning
confidence: 99%
“…This subtle difference between the versions may suggest either subtle cultural differences or reflect an effect of aging. The Chinese participants in the present sample were younger than the Caucasian participants in the studies evaluating the original English COHS (Ersche et al, 2017;Ersche et al, 2019) and previous studies suggest that younger adults may undergo a period of stronger stimulus-response learning (Juncos-Rabadan, Pereiro, & Facal, 2008;Mell et al, 2005) to support both routine and automatic behaviors based on context-dependent association.…”
Section: Discussionmentioning
confidence: 50%
“…Self-report measures were designed and presented using the Qualtrics software. Total scores were obtained from the CFI (Dennis & Vander Wal, 2010; 20 items, α = .86), the Cognitive Flexibility Scale (CFS; Martin & Rubin, 1995; 12 items, α = .77), and the Creature of Habit Scale (COHS; Ersche, Lim, Ward, Robbins, & Stochl, 2017; 27 items, α = .85). We also computed scores for the two subscales of the COHS (i.e.…”
Section: Assessment Of Cognitive Flexibilitymentioning
confidence: 99%